2021
DOI: 10.1002/fes3.299
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐annual climate variability constrains rice genetic improvement in China

Abstract: Yield potential has been significantly increased through hybrid rice breeding in the past, however, the genetic gain in grain yield is becoming marginal in recent years, especially in farmers' field. The increase in climate variability is one potential reason for the stagnant rice grain yield. Moreover, overuse of nitrogen fertilizer and poor grain quality of hybrid rice reduce its advantage over inbred rice. The present study evaluated seventy-eight elite hybrid varieties in 2014-2018 aiming to determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 58 publications
(73 reference statements)
1
5
1
Order By: Relevance
“…For example, JLYHZ had the highest yield stability while JLY1212 had the lowest yield stability across years (Table 1). Previous studies have demonstrated that variations in grain yield across different planting years are mainly associated with the variations in temperature in central China [29]. In this study, OsHSBP2, a negative regulator of heat shock response [43], was down-regulated in LLYHZ compared with JLYHZ and JLY1212 (Table S5).…”
Section: Physiological and Molecular Traits Limiting The Grain Yield ...mentioning
confidence: 57%
See 1 more Smart Citation
“…For example, JLYHZ had the highest yield stability while JLY1212 had the lowest yield stability across years (Table 1). Previous studies have demonstrated that variations in grain yield across different planting years are mainly associated with the variations in temperature in central China [29]. In this study, OsHSBP2, a negative regulator of heat shock response [43], was down-regulated in LLYHZ compared with JLYHZ and JLY1212 (Table S5).…”
Section: Physiological and Molecular Traits Limiting The Grain Yield ...mentioning
confidence: 57%
“…The nitrogen uptake at each growth stage was calculated as the sum of N contents in each organ. The grain protein content was determined by multiplying the N concentration with 5.95 [29]. The nitrogen harvest index (NHI) was calculated as the ratio of N accumulation in grain over the total aboveground N uptake.…”
Section: Plant Sampling and Measurementmentioning
confidence: 99%
“…Except for amylose content, protein content is another index affecting cooking and eating quality, because many studies have reported a significantly negative correlation between protein content and cooking and eating quality in rice [19,21]. Furthermore, protein content is an important index for evaluating the nutritional quality of rice [18]. In the present study, compared with no shading, shading at the booting stage and shading at the grain filling stage significantly increased the protein content of rice, which was in line with the results of previous studies [22,44].…”
Section: Effects Of Shading At the Booting And Grain Filling Stages O...mentioning
confidence: 99%
“…A significantly positive correlation between amylose content and light intensity in rice has been observed [17]. As the second largest storage substance in rice endosperm, protein content determines the nutritional quality of rice [18]. Significant and negative correlations between grain protein content and cooking and eating quality have been widely observed in rice [19][20][21].…”
Section: Introductionmentioning
confidence: 97%
“…Grain yield and grain protein content are important traits for wheat production, but they are usually negatively correlated [67][68][69]. This is related to the fact that protein synthesis requires more energy and photosynthetic products than carbohydrate synthesis, or it may be attributed to the dilution effect of carbohydrates on grain protein [70].…”
Section: Irrigation and Nitrogen Affect Yield And Grain Storage Prote...mentioning
confidence: 99%